(3eHGOF GdJShjb (B:s (3eONd eYGUQ (B/s - (3UHQI, SeQ Jhajbs ((3YeGf(B: s (3OGQ GdGYUGQ GdYdej(B, s, 2010)
(3ebOeI aj GdJShjb , GdHjFI GdJShjbjI , JbSje GdShb , Sdhc GdeSJgdc , SjGSGJ h bQGQdJ GdSdY , JWhjQ GdSdY GdLOjOI , GdJSYjQ , GdJhRjY , GdJQhjL , GdJShjb GdGdcJQhfj (B.s
(3eQGLY U(B.231s
Keywords: (3COGQI GdeHjYGJs; (3GdHjFI GdJShjbjIs; (3GdJShjbs; (3GdJShjb GdGdcJQhfjs